DTH RECEPTION SYSTEM WITH SMALL APERTURE ANTENNA FOR KU-BAND SATELLITE BROADCAST RECEPTION - Caner, Dogan Hakan (My University, 2012)
The scope of this study is the development of a novel demonstrator reception system with a phased array antenna system mainly focuses on the development of the control software for the antenna steering and the subsequent testing of these methods. Within this thesis, a geostationary satellite broadcast reception system in Ku-band with a smaller antenna size under the conditions limited by adjacent satellite interferers for DTH reception is investigated. Reduced antenna size at the receiver side causes more interference from adjacent satellites operating at the same frequency range. Implementing a multi input reception system with joint detection can be used to detect and mitigate the interference caused by unwanted satellites. Multi input reception system can also be used to tolerate the pointing errors and opportunity to provide selectivity among the satellites inside the coverage area. This approach is both studied in a simulation environment and also on the demonstrator setup. In the simulation phase, different beamforming algorithms are tested under different reception scenarios with different antenna sizes and feed alignments. On the demonstrator part the results gained from simulations are applied and the system performance is evaluated.
Keywords: MLNB; DTH; Beam Forming; fi=Tietoliikennetekniikka|en=Telecommunications Engineering|; fi=Master's Degree Programme in Telecommunication Engineering|en=Master's Degree Programme in Telecommunication Engineering|